Computer science - theory and applications : Third International Computer Science Symposium in Russia, CSR 2008, Moscow, Russia, June 7-12, 2008 : proceedingsSymposium in Russia, CSR 2008, Moscow, Russia, June 7-12, 2008, Proceedings - Hirsch, Edward A. (Springer, 2017)
This book constitutes the refereed proceedings of the Third International Computer Science Symposium in Russia, CSR 2008, held in Moscow, Russia, June 7-12, 2008. The 33 revised papers presented together with 5 invited papers and one opening lecture were carefully reviewed and selected from 103 submissions. All major areas in computer science are addressed. The theory track deals with algorithms, protocols, and data structures; complexity and cryptography; formal languages, automata and their applications to computer science; computational models and concepts; proof theory and applications of logic to computer science. The application part comprises programming and languages; computer architecture and hardware design; symbolic computing and numerical applications; application software; artificial intelligence and robotics.